Technology acceptance and usage behaviour of content and language integrated learning teachers in Turkey - Koç, Özge; Yüksel, Hatice Gülru; Altun, Emin (Universitas Ahmad Dahlan, 2021)
Content and language integrated learning (CLIL) is an approach that combines content and language objectives. Despite substantial expansion over the past two decades, its successful adoption raises several challenges for teachers. Teachers turn to information and communication technologies (ICT) to solve their problems. This study aims to investigate technology acceptance and use of English language teachers adopting the CLIL approach in Turkey, and to identify the difficulties they encounter while integrating technology into practice. The study is explanatory in research design and employs the Technology Acceptance Model (TAM) developed by Davis (1989) as a framework. A 27-item Likert-type questionnaire was used to gather data from 61 teachers practicing in private and public schools. The results showed a statistically significant difference in technology integration intention and use behaviors of teachers. The qualitative data suggested that among the difficulties faced by CLIL teachers were facilitating environments, managerial assistance, and teacher technology awareness.